2007
DOI: 10.1002/biot.200600101
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous expression and characterization of recombinant glycerol dehydratase from Klebsiella pneumoniae in Escherichia coli

Abstract: Glycerol dehydratase (EC 4.2.1.30), as one of the key enzymes in converting glycerol to the valuable intermediate 1,3-propanediol, is important for biochemical industry. The dhaB genes encoding coenzyme B(12)-dependent glycerol dehydratase in Klebsiella pneumoniae were cloned and expressed in Escherichia coli. An effective co-expression system of multiple subunits protein was constructed. Heterologous expression vectors were constructed using the splicing by overlap extension-PCR technique to co-express the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 23 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Wang et al (2007) tried to fuse the three subunits of GDH together in tandem but the resulting fusion protein showed lower activity compared to the wild-type enzyme. In this study, the N-terminal of the b-subunit was fused to the C-terminal of either a-or c-subunit with or without the insertion of a linker peptide through gene splicing.…”
Section: Discussionmentioning
confidence: 96%
“…Wang et al (2007) tried to fuse the three subunits of GDH together in tandem but the resulting fusion protein showed lower activity compared to the wild-type enzyme. In this study, the N-terminal of the b-subunit was fused to the C-terminal of either a-or c-subunit with or without the insertion of a linker peptide through gene splicing.…”
Section: Discussionmentioning
confidence: 96%
“…Direct expression, coexpression, and fusion expression methods were used for heterologous expression and characterization of GDHt from K. pneumoniae in E. coli , and the activities of three heterologous expression products were found to be 27.4, 2.3, and 0.2 U/mg, respectively. It was demonstrated that the highest enzyme activity was almost 17 times of that in K. pneumoniae [ 92 ], while these researches had always focused on only one enzyme. These methods could be used for the coexpressions of dhaB and dhaT genes to efficiently convert glycerol to 1,3-PD, and even in other bioconversion processes involving multienzymatic coexpressions, such as coexpressions of the GDHt, PDOR, and the reactivating factor.…”
Section: Glycerol Dehydratasementioning
confidence: 99%
“…To verify the activity of our engineered enzyme, we began by determining its specific activity over a range of temperatures. The optimum temperature (T opt ) for the unlinked enzyme is 37 C. [32] Our linked variant, KpGDHt-L, was substantially more active at higher temperatures, displaying a T opt of 57 C ( Figure 1A). Consistent with the activity data, differential scanning fluorimetry showed a midpoint for unfolding (T m ) at 58 C ( Figure 1B).…”
Section: Linked Kpgdht Variant With Enhanced Thermostabilitymentioning
confidence: 99%